2012
DOI: 10.3233/jad-2012-120229
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Silencing and Plasma Membrane Dyshomeostasis Induced by Amyloid-β Peptide are Prevented by Aristotelia chilensis Enriched Extract

Abstract: Alzheimer's disease (AD) is characterized by the presence of different types of extracellular and neurotoxic aggregates of amyloid-β (Aβ). Recently, bioactive compounds extracted from natural sources showing neuroprotective properties have become of interest in brain neurodegeneration. We have purified, characterized, and evaluated the protective potential of one extract enriched in polyphenols obtained from Aristotelia chilensis (MQ), a Chilean berry fruit, in neuronal models of AD induced by soluble oligomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 55 publications
3
15
0
Order By: Relevance
“…Using this approach, it has been found that medial septal neurons lose their theta firing coherence upon A β application [ 66 ]. This effect has been evaluated in cultured neurons that exhibit synchronous spontaneous calcium transients [ 67 70 ], showing that either increasing A β production by transfecting the cultures with the human APP gene [ 69 ] or by directly applying A β to the culture medium drastically reduced the synchronized neuronal calcium oscillations [ 67 , 68 , 70 ]. Recently, calcium imaging has also been used in vivo to evaluate neural activity, either in the hippocampal CA1 region or in the cortex of the double transgenic mice expressing APPswe and mutated presenilin 1 (G384A) [ 30 , 31 ].…”
Section: Other Alterations In Neural Population Activity Induced Bmentioning
confidence: 99%
“…Using this approach, it has been found that medial septal neurons lose their theta firing coherence upon A β application [ 66 ]. This effect has been evaluated in cultured neurons that exhibit synchronous spontaneous calcium transients [ 67 70 ], showing that either increasing A β production by transfecting the cultures with the human APP gene [ 69 ] or by directly applying A β to the culture medium drastically reduced the synchronized neuronal calcium oscillations [ 67 , 68 , 70 ]. Recently, calcium imaging has also been used in vivo to evaluate neural activity, either in the hippocampal CA1 region or in the cortex of the double transgenic mice expressing APPswe and mutated presenilin 1 (G384A) [ 30 , 31 ].…”
Section: Other Alterations In Neural Population Activity Induced Bmentioning
confidence: 99%
“…Actually, the nutritional and phytochemical characterization of this fruit, as well as its biological properties, have suggested the capacity of maqui anthocyanins to modulate hyperglycemia and insulin sensitivity [4] as well as to inhibit mechanisms involved in the absorption of sugars [5]. Moreover, other phenolic compounds present in maqui are also responsible for the high antioxidant capacity and the ability to inhibit adipogenesis and inflammation [16,17], thus decreasing oxidative stress and providing cardioprotective and neuroprotective effects [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are responsible of their intense blackish colour and the major contributor to their antioxidant potential, which is one of the highest among known berry fruits of the entire world. 12 Many studies have linked anthocyanins content in maqui berry with its wide biological activities such as anti-diabetic effects, 13 prevention of Alzheimer's disease, 14 inhibition of adipogenesis and inflammation, 10 prevention against oxidative stress 15 and prevention of low-density lipoprotein oxidation. 12 Whilst there are several works, in the scientific literature, reporting the biological effects and the anthocyanins contents of berry fruits in general and maqui berry in particular, there is lack of information regarding the phenolic acids and flavonoids presents in this fruit.…”
Section: Introductionmentioning
confidence: 99%